(untitled) (Journal of history, 2022)
The article discusses the methodological foundations of the study of the history of Soviet Kazakhstan based on the analysis of historiographic sources. The opinions of historians on the theoretical and methodological basis on the problems of periodization of Russian history are analyzed. The author’s view on the name of the history of Soviet Kazakhstan is shown. The conclusions of scientists of the Soviet and post-Soviet periods on the problems of periodization of the history of Kazakhstan are revealed. The point of view of M.K. Kozybaeva, T. Omarbekova on the division of the history of Kazakhstan into eras and periods. The review is carried out on the model of periodization of Kh. Abzhanov, Z. Kinayatuly, Zh. Artykbaev. Describes the division by historians into periods and stages of individual problems in their study. The principles, methods and criteria necessary for studying the problems of periodization are analyzed. On this basis, the periods and stages of the history of Soviet Kazakhstan recommended by the author of the article are shown and characterized. The approaches to the study of the history of Soviet Kazakhstan and the current situation in science under the conditions of a totalitarian system are described. Determine the consequences of adherence to the Marxist-Leninist methodology, the class approach. Shows the requirements in the period of “thaw” and stagnation in society, the situation in science in the years of perestroika. Methodological approaches are considered in line with the revision of history, the formation of new historical knowledge. Concepts and approaches to studying the history of Soviet Kazakhstan and the rationality of their application are revealed. Key words: history of Soviet Kazakhstan, science, methodology, periodization, principles, period, stage, approach, research.